The past laws of nations: Memory, identity and legislation in international disputes over cultural property - Rojas, Agustín (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2022)
Based on a dialogue between two well-known sub-disciplines, cultural history and legal anthropology, the following article explores recent disputes involving various groups and related institutions in the global South and their historical claims to cultural property, the right to its curatorship, attempts to facilitate restitution and tensions within international organisations. To this end, I shall examine and compare four lawsuits brought against the British Museum in recent years by the states of Chile, Egypt, Nigeria and Greece, demanding the restitution of objects that they claim form part of the cultural heritage of their communities. This provides a glimpse of the enormous legal, historical, ethical and political challenges involved in examining disputes that span controversial horizons and require clear definitions within the framework of overlapping discordant systems, all of which renders these conflicts uncomfortable and challenging for the international community as a whole.